2002
DOI: 10.1002/pds.745
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prescribed drug doses after market introduction

Abstract: SUMMARYPurpose The establishment of recommended dosing regimens has always been a difficult aspect of drug development. This paper examines the extent to which postmarketing prescribing deviates from initially recommended dosing regimens. We used the World Health Organization's (WHO) periodically updated compilation of the 'Defined Daily Dose' (DDD) to reflect prevailing patterns of prescribing in national markets. The aim of this study was to evaluate DDD changes over time (1982)(1983)(1984)(1985)(1986)(1987)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 17 publications
3
41
0
Order By: Relevance
“…In this study, the decade of registration was a strong predictor for undergoing a DDD change; this was also found in our previous study [4]. The reason for this could be that, because of the extensive experience with drugs marketed before 1970, good dosing strategies had already been developed in clinical practice long before the DDD methodology was introduced in the mid-1970s.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In this study, the decade of registration was a strong predictor for undergoing a DDD change; this was also found in our previous study [4]. The reason for this could be that, because of the extensive experience with drugs marketed before 1970, good dosing strategies had already been developed in clinical practice long before the DDD methodology was introduced in the mid-1970s.…”
Section: Discussionsupporting
confidence: 79%
“…When Cross et al studied labelling changes of New Molecular Entities in the United States approved by the Food and Drug Administration between 1980 and 1999, they found that one in five compounds underwent a dosage change after marketing [3]. Our group has previously reported on 115 changes in the defined daily dose (DDD)-a dose measure developed and maintained by the World Health Organization (WHO)-and came basically to the same conclusion [4]. DDD increases were most frequently associated with antibiotics, while cardiovascular drugs underwent more dose decreases.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations